Bridal Anxieties: Politics of Gender, Neoconservatism and Daytime TV in Turkey - Sayan-Cengiz, Feyda (Female Agencies and Subjectivities in Film and Television, 2020)
This chapter analyzes the reflections of Turkey’s neoconservative and neoliberal politics of gender on daytime television. The focus is on Bridal House, a popular daytime TV show in Turkey which interpellates women as domestic subjects competing with other women to prove their domestic abilities, particularly the ability to navigate the etiquette of domestic consumption. Hierarchies are instigated among women through symbolic battles on “tasteful” consumption, and the marital household surfaces as a space of constant regulation where women strive to be ideal housewives. By analyzing Bridal House through a Bourdieusian framework, this chapter traces the representations of the “ideal female subject” along neoconservative and neoliberal lines, and demonstrates the ways in which symbolic violences are enacted on women in contemporary Turkey’s daytime TV culture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Entertaining Africans: Creative Innovation in the (Internet) Television Space - Dovey, Lindiwe (Television in Africa in the Digital Age, 2021)
Despite great heterogeneity, the vast continent of Africa and the diverse people of its countries and diasporas have often been represented through the most reductive, essentialising, and denigrating paradigms— a process that Nigerian writer Chimamanda Adichie Ngozi has referred to as “the danger of a single story”. One of the most dangerous of these paradigms is the developmentalist one, which shoehorns Africa into a western, capitalist teleological framework that overlooks and denies Africa’s production of and participation in forms of leisure, pleasure and entertainment.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 3-Afrique (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Identités diasporiques; Royaume-Uni (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

Representing Black Britain: Black and Asian Images on Television - Malik, Sarita (SAGE Publications, Limited, 2001)
'One of the most important books on race, representation and politics to come along in a decade' - Henry Giroux, Penn State University Representing Black Britain offers a critical history of Black and Asian representation on British television from the earliest days of broadcasting to the present day.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; Royaume-Uni (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

The Paramilitary Hero on Turkish Television: A Case Study on Valley of the Wolves - Çetin, Berfin Emre (Cambridge Scholars Publisher, 2015)
The Paramilitary Hero on Turkish Television: A Case Study on Valley of the Wolves explores the representation and reception of nationalism and masculinity in Turkey through an examination of the popular television serial, Valley of the Wolves which has been aired on Turkish television since 2003. This detailed examination of the show demonstrates a particular discourse of nationalism, namely the Turkish Islam synthesis embedded in a gender-specific regime in which the paramilitary hero is placed at the centre. The study draws on thirty-seven in-depth interviews with viewers of the programme from different social backgrounds. These viewers read the serial from various perspectives in the light of their gendered experiences, suggesting that the relationship between text and audience is not necessarily predetermined by the former, but is rather constructed through an interdiscursive process. The book also examines the pleasures of the “contesting” readers of Valley of the Wolves, drawing on the audience interviews, and argues that critical approaches to a particular media text do not present a barrier to audience pleasures.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Russian Overlords, Vodka, and Logoffski: Russian- and English- Language Discourse About Anti-Russian Xenophobia in the EVE Online Community - Goodfellow, Catherine (Games and Culture, 2015)
This article explores the attitudes of EVE Online players toward their Russian counterparts. Popular community opinion paints Russian players as aggressive, cliquish and hostile, and as cheats who exploit the game in order to make (real-world) money. The article also analyzes the ways in which Russian pilots challenge, subvert, and discuss these attitudes. Two key arguments are presented. First, that although perceptions of Russian EVE players are often negative, these discourses in EVE are complicated by the fact that aggression, organization, and tight player groups are prerequisites for success within the game. Second, the opinions and agency of Russian players are highlighted. By examining both Russian- and English-language discussions, we see that rather than being silent victims of discrimination, or economic migrants “ruining” the game for other players, Russian pilots inhabit a complex space in a community engaged in two-way dialogue about culture, ethnicity, and play practices in EVE.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice

The Routledge Companion to Media and Race - Campbell, Christopher (Routledge Companions, 2017)
"The Routledge Companion to Media and Race serves as a comprehensive guide for scholars, students, and media professionals who seek to understand the key debates about the impact of media messages on racial attitudes and understanding. Broad in scope and richly presented from a diversity of perspectives, the book is divided into three sections: first, it summarizes the theoretical approaches that scholars have adopted to analyze the complexities of media messages about race and ethnicity, from the notion of 'representation' to more recent concepts like Critical Race Theory. Second, the book reviews studies related to a variety of media, including film, television, print media, social media, music, and video games. Finally, contributors present a broad summary of media issues related to specific races and ethnicities and describe the relationship of the study of race to the study of gender and sexuality"--Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

Independent Videogames: Cultures, Networks, Techniques And Politics - Ruffino, Paolo (Routledge, 2021)
Independent Videogames investigates the social and cultural implications of contemporary forms of independent video game development. Through a series of case studies and theoretical investigations, it evaluates the significance of such a multi-faceted phenomenon within video game and digital cultures. A diverse team of scholars highlight the specificities of independence within the industry and the culture of digital gaming through case studies and theoretical questions. The chapters focus on labor, gender, distribution models and technologies of production to map the current state of research on independent game development. The authors also identify how the boundaries of independence are becoming opaque in the contemporary game industry – often at the cost of the claims of autonomy, freedom and emancipation that underlie the indie scene. The book ultimately imagines new and better narratives for a less exploitative and more inclusive videogame industry. Systematically mapping the current directions of a phenomenon that is becoming increasingly difficult to define and limit, this book will be a crucial resource for scholars and students of game studies, media history, media industries and independent gaming.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

War Games: Memory, Militarism and the Subject of Play - Hammond, Philip; Pötzsch, Holger (Bloomsbury Publishing USA, 2019)
Many of today's most commercially successful videogames, from Call of Duty to Company of Heroes, are war-themed titles that play out in what are framed as authentic real-world settings inspired by recent news headlines or drawn from history. While such games are marketed as authentic representations of war, they often provide a selective form of realism that eschews problematic, yet salient aspects of war. In addition, changes in the way Western states wage and frame actual wars makes contemporary conflicts increasingly resemble videogames when perceived from the vantage point of Western audiences.This interdisciplinary volume brings together scholars from games studies, media and cultural studies, politics and international relations, and related fields to examine the complex relationships between military-themed videogames and real-world conflict, and to consider how videogames might deal with history, memory, and conflict in alternative ways. It asks: What is the role of videogames in the formation and negotiation of cultural memory of past wars? How do game narratives and designs position the gaming subject in relation to history, war and militarism? And how far do critical, anti-war/peace games offer an alternative or challenge to mainstream commercial titles?
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Queerness in Play - Harper, Todd; Adams, Meghan Blythe; Taylor, Nicholas (Palgrave Macmillan, 2018)
"Queerness in Play examines the many ways queerness of all kinds - from queer as 'LGBT' to other, less well-covered aspects of the queer spectrum - intersects with games and the social contexts of play. The current unprecedented visibility of queer creators and content comes at a high tide of resistance to the inclusion of those outside a long-imagined cisgender, heterosexual, white male norm. By critically engaging the ways games - as a culture, an industry, and a medium - help reproduce limiting binary formations of gender and sexuality, Queerness in Play contributes to the growing body of scholarship promoting more inclusive understandings of identity, sexuality, and games."--Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Who Made Your Phone? Compassion and the Voice of the Oppressed in Phone Story and Burn the Boards - Navarro-Remesal, Víctor; Zapata, Beatriz Pérez (Open Library of Humanities, 2018)
Burn the Boards (Causa Creations, 2015) portrays the life of an Indian worker who recycles electronic waste in a precarious environment. Phone Story (Molleindustria, 2011) simulates the journey and process of production and consumption of mobile phones, from Congo and China to Pakistan. Whereas Phone Story is described as ‘an educational game’ that addresses the player directly as a consumer, Burn the Boards is a resource management puzzle that creates compassion through role playing. These games bring to the fore a hidden reality of the everyday that is ingrained in historical relationships and power dynamics, drawing attention to what Michael Rothberg has recognized as ‘exploitation in an age of globalized neo-liberal capitalism’ (2014: iv).  This article explores how these games denounce the smartphone industry by using that same technology. For this purpose, we refer to Game Studies theory on procedural rhetoric; values and ethics; and the role of the player, combined with questions of (neo)colonization, globalization, and neoliberalism drawn from Postcolonial Studies. Our analysis shows the complicity of users and their confrontation with the extreme vulnerability of others, emphasizing how the coloniality of power works in our global consumer society. Thus we study the power relationships described and established by these games, the affective reactions which they seek to trigger, and their potential to transform players from passive observers into ethical players and consumers.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Gaming Representation: Race, Gender, and Sexuality in Video Games - Malkowski, Jennifer; Russworm, TreaAndrea M. (Indiana University Press, 2017)
Gaming Representation' offers a timely and interdisciplinary call for greater inclusivity in video games. The issue of equality transcends the current focus in the field of Game Studies on code, materiality, and platforms. Journalists and bloggers have begun to hold the digital game industry and culture accountable for the discrimination routinely endured by female gamers, queer gamers, and gamers of color. Video game developers are responding to these critiques, but scholarly discussion of representation in games has lagged behind. Contributors to this volume examine portrayals of race, gender, and sexuality in a range of games, from casuals like Diner Dash, to indies like Journey and The Binding of Isaac, to mainstream games from the Grand Theft Auto, BioShock, Spec Ops, The Last of Us, and Max Payne franchises. Arguing that representation and identity function as systems in games that share a stronger connection to code and platforms than it may first appear, 'Gaming Representation' pushes gaming scholarship to new levels of inquiry, theorizing, and imagination.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créatrice; _Nettoyé

Queer Game Studies - Ruberg, Bonnie; Shaw, Adrienne (University of Minnesota Press, 2017)
The in-depth, diverse, and accessible essays in Queer Game Studies use queerness to challenge the ideas that have dominated gaming discussions. This volume reveals the capacious albeit underappreciated communities that are making, playing, and studying queer games, demonstrating the centrality of LGBTQ issues to the gamer world and establishing an alternative lens for examining this increasingly important culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé

The Current State of Muslim Representation in Video Games - Khan, Imad; Khalaf, Farah; Ismail, Rami; Ramzan, Romana (2016)
Muslim members of the video game industry discuss the current state of Muslim representation within video games. This includes current problems with the way Muslims are represented and potential solutions. Our panelists come from all sides of the industry. From AAA, to indie, the panelists all have a unique voice and angle they would like to bring to the discussion. All panelists have grown up Muslim in western countries and have had to deal with certain adversities and challenges. It's through that experience that the panelists want to bring a lively discussion, backed with personal accounts and sources, that is not only engaging, but educational.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play -- the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé